Constitute the passive infrastructure in network - YANG Shu-fan1; LI Fang-min1; ZHU Jian-qiu2; LIU Xin-fen 3 (Tongxin xuebao)
Only with passive technology on network security , it is impossible to build a soundly secretive application. There are many disadvantages in practice. In order to set up a more firm security network, we must take advantage of active technology. This paper presents us how to build a security network system with active technology, make use of decoy sever to allure and track the attackers. In the procedure, a data analysis model is also brought out. It proves that the active technology is very helpful to forecast attack activities and promote network security with passive technology.